ANALISIS SEKTORAL DAN SPASIAL SEKTOR UNGGULAN KABUPATEN PONTIANAK TAHUN 2008-2012 - , Hardiyansyah; , Tri Widodo, Prof. M.Ec.Dev., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study has several objectives related to economic base in local development planning in Pontianak Regency. Firstly, to identify the sector base contained in each sub district using Symmetric Location Quotient (SLQ) method. Secondly, to analyze the dynamics specialization and dynamics despecialization of sub districtâs comparative advantage applying econometric models. Thirdly, to analyze the shifting patterns of its comparative advantage and the pattern of its linkages using Spearman Rank Correlation. The type of data are secondary data, in the form of Gross Domestic Product (GDP) Pontianak Regency year 2008-2012 (the period after the last expansion in Pontianak Regency). The analysis is carried out to combine the sectoral approach and spatial approach in nine sub districts in Pontianak Regency as the unit of analysis. Conclusions from the study revealed that the SLQ index calculation is optimal for analyzing the dynamics of the sector base and comparative advantage within the framework of regional analysis. Dynamics specialization that occured not only due to the high level of GDP of the sector in the economy of the sub district, but also caused by dynamic changes of GDP to GDP in the same sector in Pontianak Regency. Rankings shift occurred more dynamic in the sub district that has a comparative advantage in the primary sector and it is due to the dynamics specialization and despecialization in the sub district or regency. Furthermore, the analysis shows the spatial relationship between sub districts in Pontianak. This conclusion reaffirms the theories and previous studies which revealed that comparative advantage should be assessed in a dynamic sense.